2019
DOI: 10.4187/respcare.07002
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Methodology for Ultrasound Evaluation of Pharyngeal Residue in the Pyriform Sinus and Epiglottic Vallecula

Abstract: BACKGROUND: Assessing the presence of pharyngeal residue in the pyriform sinus and epiglottic vallecula is important because insufficient pharyngeal clearance is a risk factor for aspiration pneumonia. Improvements in the performance of ultrasound to visualize the pyriform sinus and epiglottic vallecula are needed. The aim of this study was to establish a method to visualize the pyriform sinus and epiglottic vallecula with ultrasound to detect pharyngeal residue. METHODS: We used real-time virtual sonography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Ultrasonography has been used for the observation of swallowing function by hyoid bone displacement and the volume of muscles related with swallowing [14,15]. Since there has been no standard procedure to observe aspiration or pharyngeal residue by ultrasonography, we recently developed a ultrasound-based direct observation method for this purpose [16,17]. We also confirmed that ultrasound can observe the incidence of aspiration and presence or absence of pharyngeal residue with high sensitivity when VFSS was as references [16,17].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Ultrasonography has been used for the observation of swallowing function by hyoid bone displacement and the volume of muscles related with swallowing [14,15]. Since there has been no standard procedure to observe aspiration or pharyngeal residue by ultrasonography, we recently developed a ultrasound-based direct observation method for this purpose [16,17]. We also confirmed that ultrasound can observe the incidence of aspiration and presence or absence of pharyngeal residue with high sensitivity when VFSS was as references [16,17].…”
Section: Introductionsupporting
confidence: 59%
“…Since there has been no standard procedure to observe aspiration or pharyngeal residue by ultrasonography, we recently developed a ultrasound-based direct observation method for this purpose [16,17]. We also confirmed that ultrasound can observe the incidence of aspiration and presence or absence of pharyngeal residue with high sensitivity when VFSS was as references [16,17]. However, ultrasound observation is inferior to VESS or FEES as nonvisualization of some important information is observed by VESS or FESS (e.g., amount of residues, starting timing of swallowing).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of detecting pharyngeal residue in the pyriform sinus was 92.0%, and the specificity was 71.9% . The sensitivity of detecting pharyngeal residue in the epiglottic vallecula was 86.7%, and the specificity was 63.6% . Moreover, swallowing care guided by frequent ultrasound examinations during mealtimes had a trend of reducing the frequency of aspiration and residue in a randomized controlled trial .…”
Section: Comparison Of Swallowing Evaluation Methodsmentioning
confidence: 95%
“…The sensitivity of aspiration detection was 0.64, and the specificity was 0.84 . Pharyngeal residue in the pyriform sinus and epiglottic vallecula is detected as high‐echogenicity areas in B‐mode video ultrasonography . The sensitivity of detecting pharyngeal residue in the pyriform sinus was 92.0%, and the specificity was 71.9% .…”
Section: Comparison Of Swallowing Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation